Biodiversitas Mikroba Rizosfer Tanaman Jeruk Keprok Borneo Prima (Citrus reticulata cv Borneo Prima) - Purwati Purwati; Hamidah Hamidah (Agrifarm : Jurnal Ilmu Pertanian, 2018)
Borneo Prima tangerine (Citrus reticulata cv Borneo Prima) is an indigenous plant from Tanjung Labu Village, Rantau Pulung District, East Kutai District, East Kalimantan Province. In the cultivation of these plants, there are pathogens that can cause a decrease in crop yields. This study aims to identify the diversity of rhizosphere microbial populations in Borneo Prima tangerine plants. The study was conducted at the Laboratory of Plant Pests and Diseases of the Faculty of Agriculture, Mulawarman University Samarinda in February-April 2018. This study was descriptive, using a survey method. The study consisted of two stages, namely (1) soil sampling on Borneo Prima tangerine citrus land in Makroman Village, Kutai Kartanegara Regency, East Kalimantan (2) isolation, characterization, identification, gram test, in the Laboratory of Pests and Plant Diseases. The data obtained were analyzed using quantitative descriptive analysis. The results of the study of the isolation of rhizosphere microbes in Borneo Prima tangerine citrus plants obtained 1 family of bacteria namely Azotobacteraceae and 4 fungal genera including Aspergilus, Mucor, Penicillium and Trichoderma. Microbes that belong to the group that benefit the soil ecosystem are Azotobacteraceae because they play a role in fixing (fixation) N2 or as biofertilizers. While the genus Mucor and Penicillium act as decomposers and Trichoderma acts as a controller of pathogens or biological agents and biological pesticides (biopestiside).